Follow-up of premalignant lesions in patients at risk for progression to gastric cancer - den Hoed, C. M.; Holster, I. L.; Capelle, L. G.; de Vries, A. C.; den Hartog, B.; ter Borg, F.; Biermann, K.; Kuipers, E. J. (Endoscopy, 2013)
Background and study aims: A recent international guideline recommends surveillance of premalignant gastric lesions for patients at risk of progression to gastric cancer. The aim of this study was to identify the role of the distribution and severity of premalignant lesions in risk categorization. Patients and methods: Patients with a previous diagnosis of atrophic gastritis, intestinal metaplasia, or low grade dysplasia were invited for surveillance endoscopy with non-targeted biopsy sampling. Biopsy specimens were evaluated by pathologists (four general and one expert) using the Sydney and the operative link for gastric intestinal metaplasia (OLGIM) systems, and scores were compared using kappa statistics.Results: 140 patients were included. In 37 % (95 % confidence interval [CI] 29 % – 45 %) the severity of premalignant lesions was less than at baseline, while 6 % (95 %CI 2 % – 10 %) showed progression to more severe lesions. Intestinal metaplasia in the corpus was most likely to progress to more than one location (57 %; 95 %CI 36 % – 76 %). The proportion of patients with multilocated premalignant lesions increased from 24 % at baseline to 31 % at surveillance (P = 0.014). Intestinal metaplasia was the premalignant lesion most frequently identified in subsequent endoscopies. Intestinal metaplasia regressed in 27 % compared with 44 % for atrophic gastritis and 100 % for low grade dysplasia. Interobserver agreement was excellent for intestinal metaplasia (k = 0.81), moderate for dysplasia (k = 0.42), and poor for atrophic gastritis (k < 0). Conclusions: Premalignant gastric lesions found in the corpus have the highest risk of progression, especially intestinal metaplasia, which has excellent interobserver agreement. This supports the importance of intestinal metaplasia as marker for follow-up in patients with premalignant gastric lesions.